Enzyme-Assisted Fluorescence Biosensor Based on Circular Single-Stranded DNA Without Group Modification for MicroRNA Detection - Xiaoxue Yin; Yazhen Liao; Feiyu Li; Jianbao Li; Jie Du (Biosensors)
Fluorescent biosensor, which has the characteristics of high sensitivity, specificity, and low cost, can be directly detected in physiological fluids such as blood and serum. Therefore, the development of fluorescence sensor platforms for miRNA detection has a positive effect on the prevention and treatment of various diseases. In this paper, miR-34a was selected as a biological indicator of Alzheimer’s disease (AD). We designed a circular single-stranded DNA (CSSD) biosensor, which uses two unmodified single-stranded DNA (ssDNA) with complementary ends, DNAa and DNAb, to form CSSD by DNA sequence pairing to improve thermal stability and achieve signal amplification. At the same time, CSSD can react with miR-34a, and then the DNA of the DNA–RNA chain is hydrolyzed by duplex-specific nuclease (DSN enzyme). Finally, miR-34a is released to partake in the subsequent step, thus realizing cycle amplification. By evaluating the change in fluorescence signal under the optimized conditions, we discovered that this approach exhibits impressive sensitivity, with a detection threshold reaching as low as 0.36 nM. This surpasses the performance of numerous preceding miRNA detection biosensors. Furthermore, the system displays excellent detection capabilities even in intricate settings like serum, showcasing a strong ability to differentiate and choose effectively. In summary, this is a signal-off fluorescent biosensor, which realizes the purpose of double amplification of biosensor signal by using CSSD and enzyme assistance so that it can be used as a valuable tool for early diagnosis of diseases.